Lignocellulosic Biomass Derived Carbon Supported Nickel Nanoparticles as an Efficient Catalyst for Reduction of Nitroarenes - Dr. Sunshine Dominic Kurbah; Kenneth Umdor; Ndege Simisi Clovis (Orbital: The Electronic Journal of Chemistry)
Nickel-based catalysts directing selectivity for the reduction of nitroarenes reduction have drawn a lot of attention; yet, they have not yielded considerable accomplishments. Here, we report an environmentally friendly method for synthesizing a nickel-based carbon-supported nanocatalyst that is easily synthesized using lignin residues. The carbon-supported nickel nanoparticle catalysts generated from lignocellulosic biomass were characterized by powder x-ray diffraction (XRD), energy-dispersive x-ray spectroscopy (EDS), and transmission electron microscopy (TEM). The present catalytic system not only shows outstanding performance with an excellent anilines output but also shows an environmentally friendly catalytic process with simple separation, easy operations, reuse and recycle.